48 year old man with bilateral, progressive visual loss over 20 years - Heuer, Dale; Nguyen, Randy; Yang, Michael B. (Digital Journal of Ophthalmology, 2023)
A 48-year-old Hispanic man presented at Los Angeles County/USC Medical Center after doctors in Mexico informed him that he had glaucoma. He described painless, progressive visual loss in both eyes for 20 years. He had no history of inflammation in the eyes. He had no history of trauma, blood loss, shock, or steroid use around the eyes. He denied any history of jaw claudication, scalp tenderness, headaches.